2012
DOI: 10.1369/0022155412459856
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot Immunocytochemical Localization of Somatostatin in Somatostatinoma by Widefield Epifluorescence, Super-resolution Light, and Immunoelectron Microscopy

Abstract: Quantum dot nanocrystal probes (QDs) have been used for detection of somatostatin hormone in secretory granules of somatostatinoma tumor cells by immunofluorescence light microscopy, super-resolution light microscopy, and immunoelectron microscopy. Immunostaining for all modalities was done using sections taken from an epoxy resin-embedded tissue specimen and a similar labeling protocol. This approach allowed assessment of labeling at light microscopy level before examination at super-resolution and electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Moreover, they have been adopted in areas other than ICC in order to analyse, for instance, spatial distributions of nanoparticles within cells/ tissues (Mühlfeld et al 2007(Mühlfeld et al , 2008Geiser et al 2013) and the association of viruses with the symbiotic pair of Paramecium and Chlorella (Yashchenko et al 2012). In principle, they could also be applied in immuno-quantum dot cytochemistry (e.g., Nisman et al 2012;Killingsworth et al 2012). Use of the disector and rotator tools offers the possibility for studying polarised, oriented or dividing cells and systems characterised by the movement of VOCs from one region to another (Lucocq and Gawden-Bone 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they have been adopted in areas other than ICC in order to analyse, for instance, spatial distributions of nanoparticles within cells/ tissues (Mühlfeld et al 2007(Mühlfeld et al , 2008Geiser et al 2013) and the association of viruses with the symbiotic pair of Paramecium and Chlorella (Yashchenko et al 2012). In principle, they could also be applied in immuno-quantum dot cytochemistry (e.g., Nisman et al 2012;Killingsworth et al 2012). Use of the disector and rotator tools offers the possibility for studying polarised, oriented or dividing cells and systems characterised by the movement of VOCs from one region to another (Lucocq and Gawden-Bone 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For ICC at the TEM level, alternative technical procedures and visualisation markers are available (Griffiths 1993;Roth 1996;Koster and Klumperman 2003;Nickel et al 2008;Webster et al 2008;Killingsworth et al 2012; AmiryMoghaddam and Ottersen 2013; Griffiths and Lucocq 2014). Visualisation markers include colloidal gold particles and quantum dots and these can be bound to a secondary reagent (e.g., protein A, streptavidin or IgG secondary antibody).…”
Section: Introductionmentioning
confidence: 99%
“…The 585 nm QD nanoparticles used showed bright and stable fluorescence when viewed by widefield light microscopy and were readily observed by TEM. A previous study by one of the present authors has shown QDs also to be suitable for super-resolution light microscopy 7 . Their photostability was particularly useful for extended viewing periods and long imaging exposures.…”
Section: Discussionmentioning
confidence: 49%
“…There are many different technical permutations available 5 depending on the question being asked however a common requirement is that the same structure in a single sample 6 is imaged by multiple microscopy modalities. Our particular approach to CLEM was developed for the study of archival human pathology tissue and the case used here has been well characterized and published previously 7 . The aim was firstly, to maximize the analytical data from a single biopsy or surgical sample and secondly, to use fluorescence light microscopy to help clarify the context of the immunocytochemical labeling pattern seen at the ultrastructural level.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials showed advantages to SERS due to their high surface volume ratio, good surface control, and excellent plasma performance. [ 108 ] Yang et al analyzed SERS images and corresponding spectrum of breast cancer before and after PTT treatment containing BP‐Au NSs. They identified various substances corresponding to each peak from the spectrum line, and analyzed the cause of great changes in the Raman spectrum of the same tumor tissue after near‐infrared irradiation.…”
Section: Low‐dimensional Nanomaterials For Imagingmentioning
confidence: 99%